Control of Resistant Pink Bollworm (Pectinophora gossypiella) by Transgenic Cotton That Produces Bacillus thuringiensis Toxin Cry2Ab - Tabashnik, Bruce E. (American Society for Microbiology, 2002)
Crops genetically engineered to produce Bacillus thuringiensis toxins for insect control can reduce use of conventional insecticides, but insect resistance could limit the success of this technology. The first generation of transgenic cotton with B. thuringiensis produces a single toxin, Cry1Ac, that is highly effective against susceptible larvae of pink bollworm (Pectinophora gossypiella), a major cotton pest. To counter potential problems with resistance, second-generation transgenic cotton that produces B. thuringiensis toxin Cry2Ab alone or in combination with Cry1Ac has been developed. In greenhouse bioassays, a pink bollworm strain selected in the laboratory for resistance to Cry1Ac survived equally well on transgenic cotton with Cry1Ac and on cotton without Cry1Ac. In contrast, Cry1Ac-resistant pink bollworm had little or no survival on second-generation transgenic cotton with Cry2Ab alone or with Cry1Ac plus Cry2Ab. Artificial diet bioassays showed that resistance to Cry1Ac did not confer strong cross-resistance to Cry2Aa. Strains with >90% larval survival on diet with 10 μg of Cry1Ac per ml showed 0% survival on diet with 3.2 or 10 μg of Cry2Aa per ml. However, the average survival of larvae fed a diet with 1 μg of Cry2Aa per ml was higher for Cry1Ac-resistant strains (2 to 10%) than for susceptible strains (0%). If plants with Cry1Ac plus Cry2Ab are deployed while genes that confer resistance to each of these toxins are rare, and if the inheritance of resistance to both toxins is recessive, the efficacy of transgenic cotton might be greatly extended.